Bhaṭṭanāyaka aura Abhinavagupta kī sādhāraṇīkaraṇavishayaka avadhāraṇā - Śarmā, Sulekhacandra (Devavāṇī-Parishad, Dillī, 1982)
On the principle of generalization in aesthetic experience in poetry as propounded by Rājānaka Abhinavagupta and Bhaṭṭanāyaka, classical writers on Sanskrit poetics.